High Angle Cases in Different Types of Skeletal Pattern Among Malay Orthodontic Patients - Afifah Syairah Abu Yazid; Amir Ashraf Muhammad Sukri; Syiral Mastura Abdullah; Aspalilah Alias (Ectodermal Dysplasia Group-Turkey, 2024)
Indexed by Scopus